Transcriptomic profile of microglia following inflammation-sensitized hypoxic-ischemic brain injury in neonatal rats suggests strong contribution to neutrophil chemotaxis and activation - Anna-Sophie Bremer; Nico Henschel; Hannah Burkard; Maria Eugenia Bernis; Thomas Ulas; Hemmen Sabir (Journal of Neuroinflammation)
Abstract Background Inflammation-sensitized hypoxic-ischemic brain injury significantly contributes to neonatal mortality as affected neonates do not benefit from standard cooling treatments. To get further insight into inflammatory responses involved, we experimentally investigated the immune response of microglia in an inflammation-sensitized neonatal hypoxia-ischemia (HI) model. Results Transcriptomic analysis of microglia isolated from brains following inflammation-sensitized HI brain injury revealed a strong upregulation of leukocyte recruitment and pro-inflammatory markers. Specifically, markers associated with neutrophil-mediated immune responses and chemotaxis were upregulated in the inflammation-sensitized HI group compared to the non-inflammation-sensitized HI and control groups. Serpine 1 and Selp could be identified as specifically upregulated markers indicating an acute inflammatory condition before HI injury. Conclusion Our study revealed preliminary data about a microglia population which is primed to recruit peripheral neutrophils to infiltrate the brain and mediate neutrophil immune response. We showed a contribution to neutrophil activation in case of inflammation following HI in the brain. Targeting microglia-mediated neutrophil recruitment can indicate a possible treatment approach in case of inflammation-sensitized HI brain injury.